FACTORS AFFECTING THE QUALITY OF LIFE OF COPD PATIENTS: A LITERATURE REVIEW - Sutrisno Sutrisno; Rondhianto Rondhianto; Tantut Susanto (UNEJ e-Proceeding, 2023)
Background: Chronic obstructive pulmonary disease (COPD) is one of the leading causes of morbidity and mortality worldwide. COPD causes various physical disorders, including dyspnea, physical weakness, and psychological disturbances that can impact the quality of life. This study aims to identify patients' quality of life and the factors influencing it. Methods: The method of this study is a systematic review using the PRISMA JBI Critical Appraisal Tool. The literature search used an electronic database of 3 electronic databases, namely Google Scholar, PubMed, and Scopus. The inclusion criteria include research on the quality of life of patients with COPD and articles published in English from 2018 – 2023. Data were analyzed using meta-synthesis. Results: The results of the study found 12 eligible articles. The analysis results show that the dominant factors affecting the quality of life of COPD patients are smoking status, degree of COPD, and depression. Active smoking status, severe COPD, and depression can worsen the quality of life. Family support, self-care management education, and medication adherence can improve quality of life. Family support is central because it can improve compliance and self-care management. Conclusion: Nurses' efforts to improve the quality of life of COPD patients, apart from being curative, can be carried out through preventive and promotive actions, including smoking cessation programs, increasing medication adherence, and improving self-care management through efforts to increase family social support.